Association between risk of type 2 diabetes and changes in energy intake at breakfast and dinner over 14 years: a latent class trajectory analysis from the China health and nutrition Survey, 1997–2011. Issue 7 (15th July 2021) - Ren, Xiyun; Gao, Jian; Han, Tianshu; Sun, Changhao
Abstract : Objective: This study aimed to investigate the association between the trajectories of energy consumption at dinner versus breakfast and the risk of type 2 diabetes (T2D). Design: Cohort study. Setting: The study was conducted in China. Participants: A total of 10 727 adults, including 5239 men and 5488 women, with a mean age of 42.7±11.2 years and a mean follow-up time of 9.1 years, met the study criteria and completed a questionnaire about energy intake and diabetes status from the China Health and Nutrition Survey in 1997–2011. Primary outcome measures: Participants were divided into subgroups based on the trajectories of the ratio of energy consumption at dinner versus breakfast. Cox multivariate regression models were used to explore the associations between different trajectories and the risk of T2D after adjustment for confounders and their risk factors. Mediation analysis was performed to explore the intermediary effect of triacylglycerol (TG), total cholesterol (TC), uric acid (UA) and apolipoprotein B (ApoB) between the trajectories and the risk of T2D. Results: For energy consumption at dinner versus breakfast, compared with a low-stable trajectory, the adjusted HR of T2D in low-increasing from early-stage trajectory was 1.29 (95% CI 1.04 to 1.60). TG, TC, UA and ApoB were significantly higher in low-increasing from early-stage trajectory than other trajectories and play partial regulation roles between trajectories and T2D. Conclusions: This study emphasised the harmful effect of a gradual increase in the ratio of energy consumption at dinner versus breakfast from early stage on the development of T2D and partially mediated by TG, TC, UA and ApoB, highlighting that it is necessary to intake more energy at breakfast compared with dinner to prevent T2D in adults.